Mitotic inheritance of the Golgi complex and its role in cell division. (1st September 2017) - Ayala, Inmaculada; Colanzi, Antonino
Abstract: The Golgi apparatus plays essential roles in the processing and sorting of proteins and lipids, but it can also act as a signalling hub and a microtubule‐nucleation centre. The Golgi complex (GC) of mammalian cells is composed of stacks connected by tubular bridges to form a continuous membranous system. In spite of this structural complexity, the GC is highly dynamic, and this feature becomes particularly evident during mitosis, when the GC undergoes a multi‐step disassembly process that allows its correct partitioning and inheritance by daughter cells. Strikingly, different steps of Golgi disassembly control mitotic entry and progression, indicating that cells actively monitor Golgi integrity during cell division. Here, we summarise the basic mechanisms and the molecular players that are involved in Golgi disassembly, focussing in particular on recent studies that have revealed the fundamental signalling pathways that connect Golgi inheritance to mitotic entry and progression. Abstract : Review : The mitotic partitioning of the Golgi complex is composed of individual and consecutive steps, each one controlling a specific aspect of cell division. G2‐specific unlinking of the Golgi ribbon into isolated stacks is necessary for cell entry into mitosis. Then, after mitosis onset, the disassembly of the Golgi membranes into clusters and vesicles regulates events that are necessary for successful cell duplication, such as spindle formation and chromosome segregation.